KAJIAN PEMASARAN KARET RAKYAT KECAMATAN BATIN XXIV KABUPATEN BATANGHARI - Cahyaningsih, Dyah; Napitupulu, Dompak MT; Ningsih, Rozaina (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2024)
This research is aimed to determine the description of the implementation of rubber marketing in Batin XXIV District, Batanghari Regency. This research was carried out in Batin XXIV District, Batanghari Regency in December 2022 - January 2023 with a sample size of 50 farmers. The research was done in survay, sample farmers were chosen in simple random sampling method (Simple Random Sampling) while the sample of marketing institutions using the snowball sampling method. The data was analized in descriptive method. The research results showed that the bokar traded by farmers was slab-shaped. Determination of dry rubber content (KKK) is done by visual assessment. Marketing of bokar is broadly divided into two, namely through UPPB intermediaries and through intermediary traders. There are 4 marketing channels for bokar in Batin XXIV District. The marketing functions carried out by marketing institutions in the research area include exchange functions, physical functions and facility functions.